2015
DOI: 10.1186/s13059-015-0733-y
|View full text |Cite
|
Sign up to set email alerts
|

Xist localization and function: new insights from multiple levels

Abstract: In female m ammals, one of the two X chromosomes in each cell is transcriptionally silenced in order to achieve dosage compensation between the genders in a process called X chromosome inactivation. The master regulator of this process is the long non-coding RNA Xist. During X-inactivation, Xist accumulates in cis on the future inactive X chromosome, triggering a cascade of events that provoke the stable silencing of the entire chromosome, with relatively few genes remaining active. How Xist spreads, what are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 92 publications
(174 reference statements)
3
135
0
2
Order By: Relevance
“…1A,B). A recent study has suggested that XCI processes are affected by chromosomal topology and the nuclear locality, and are not established uniformly throughout chromosomes (Cerase et al, 2015). Therefore, we expected that different insertion sites of the two reporter genes might provide different monitoring results depending on the time of development and tissues involved.…”
Section: Results and Discussion Live-cell Imaging Of Xcrmentioning
confidence: 97%
“…1A,B). A recent study has suggested that XCI processes are affected by chromosomal topology and the nuclear locality, and are not established uniformly throughout chromosomes (Cerase et al, 2015). Therefore, we expected that different insertion sites of the two reporter genes might provide different monitoring results depending on the time of development and tissues involved.…”
Section: Results and Discussion Live-cell Imaging Of Xcrmentioning
confidence: 97%
“…Interestingly, efficient splicing is more prevalent among lincRNAs that have been shown to have specific functions, such as XIST (Cerase et al 2015), FIRRE (Hacisuleyman et al 2014), and MIAT (Liao et al 2016). Indeed, efficient splicing has been shown to be necessary for some lincRNAs to carry out their function (Marquardt et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…• X chromosome silencing by XIST: a 16kB lncRNA (Cerase, et al 2015) human and mouse lncRNAs http://bioinfo.life.hust.edu.cn/lncR NASNP2…”
Section: Declaration Of Interest and Fundingmentioning
confidence: 99%